2021
DOI: 10.1007/s11886-021-01519-x
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Diseases in COVID19: a Contemporary Review

Abstract: Purpose of Review Coronavirus disease 2019 (COVID19) involves the heart, including pericardium. This article reviews the possible pathophysiological mechanisms in pericardial involvement in COVID19 and pericardial manifestations of COVID19. It also summarizes the patients with pericarditis secondary to COVID19 and outlines the contemporary treatment strategies in this patient population. Recent Findings A high degree of suspicion is required to identify the pericardial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 84 publications
0
37
0
8
Order By: Relevance
“…Post-mortem studies have identified pericarditis in about 20% of the COVID-19 cases [ 50 , 51 ] and several case reports reported acute pericarditis in patients with SARS-CoV-2 infection with typical ECG signs (diffuse ST elevation and PR depression) [52] , [53] , [54] , [55] , [56] .…”
Section: “Typical” Ecg Features Of Covid-19 Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-mortem studies have identified pericarditis in about 20% of the COVID-19 cases [ 50 , 51 ] and several case reports reported acute pericarditis in patients with SARS-CoV-2 infection with typical ECG signs (diffuse ST elevation and PR depression) [52] , [53] , [54] , [55] , [56] .…”
Section: “Typical” Ecg Features Of Covid-19 Complicationsmentioning
confidence: 99%
“…To date, the exact pathophysiological mechanism of pericardial involvement is not fully understood. As proposed mechanisms, systemic inflammatory reaction (with cytokine storm), and endothelial damage induced by COVID-19 may lead to pericardial involvement [52] . Furthermore, COVID-19 induced pericarditis might reflect the expression of ACE2 receptors in epicardial adipocites (mediating the cell entry of SARS-CoV-2) [ 17 , [61] , [62] , [63] , [64] , [65] ], and possibly triggering local inflammation [ 63 , [65] , [66] , [67] , [68] , [69] , [70] ].…”
Section: “Typical” Ecg Features Of Covid-19 Complicationsmentioning
confidence: 99%
“…Some case reports reported acute pericarditis during SARS-COV2 infection 54 . This type of cardiac involvement is often seen in patients with troponin elevation in the context of myocardial damage and less frequently as a primary presentation of COVID-19 infection which occurred most in younger patients 55 , 56 .…”
Section: Left and Right Ventricle: Major Findingsmentioning
confidence: 99%
“…In conclusion, in COVID-19 patients with high suspicion of IE or significant VHD, explorative TTE and if inconclusive a subsequent TOE is mandatory for the diagnosis with all the precautions aimed at avoiding the spread of the infectious disease. Some case reports reported acute pericarditis during SARS-COV2 infection 54 . This type of cardiac involvement is often seen in patients with troponin elevation in the context of myocardial damage and less frequently as a primary presentation of COVID-19 infection which occurred most in younger patients 55,56 .…”
Section: Cardiac Valves and Pericardiummentioning
confidence: 99%
“…SARS-CoV-2 cardiac involvement has been frequently reported, with acute myocardial infarction and pericarditis the most frequently described diseases [10][11][12]. Also, rare cases of cardiac tamponade have been quoted as a suspected isolated manifestation of COVID-19 infection [13]. However, no strong demonstration has been produced so far.…”
Section: To the Editormentioning
confidence: 99%